2021
DOI: 10.3390/antiox10101571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Apiaceae Family Spices in Ameliorating Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the most prevalent neurodegenerative diseases worldwide. In an effort to search for new strategies for treating AD, natural products have become candidates of choice. Plants are a rich source of bioactive and effective compounds used in treating numerous diseases. Various plant extracts are known to display neuroprotective activities by targeting different pathophysiological pathways in association with the diseases, such as inhibiting enzymes responsible for degrading neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…Numerous essential oils have shown promise in inhibiting cholinesterase, a key factor in AD progression. The members of the Apiaceae family have been extensively studied to substantiate their traditional medicinal uses, with a primary emphasis on elucidating their neuroprotective mechanisms [25] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous essential oils have shown promise in inhibiting cholinesterase, a key factor in AD progression. The members of the Apiaceae family have been extensively studied to substantiate their traditional medicinal uses, with a primary emphasis on elucidating their neuroprotective mechanisms [25] …”
Section: Resultsmentioning
confidence: 99%
“…The members of the Apiaceae family have been extensively studied to substantiate their traditional medicinal uses, with a primary emphasis on elucidating their neuroprotective mechanisms. [25]…”
Section: Analysis Of Ache and Bche Inhibition Activitiesmentioning
confidence: 99%
“…Further, the concentration of reduced GSH and the ratio of GSH/GSSG were found to be significantly increased, which were reduced due to scopolamine treatment [ 75 ]. The authors suggested that the antioxidant effect of UD, especially UDR, may counteract neurodegenerative diseases such as Alzheimer’s disease [ 75 , 76 ].…”
Section: Antioxidant Potential Of Udmentioning
confidence: 99%
“…Recently, the Food and Drug Administration (FDA) approved an antibody drug (Aduhelm), which may improve AD symptoms. Yet, all these allopathy drugs have associated side effects, ranging from minor headache to swelling and brain haemorrhaging [3]. In this regard, plants could provide an effective and safer source of bioactive compounds to be used as a drug.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, plants could provide an effective and safer source of bioactive compounds to be used as a drug. Researchers have identified several plants with neuroprotective properties, like AChE inhibition, retarding atypical aggregation and scavenging free radicles, which protect against oxidative stress [3][4][5]. Additionally, several bioactive compounds have anti-inflammatory properties and reduce the activity of pro-inflammatory markers (interleukins (IL-6, IL-1β), nitric oxide (NO), tumor necrosis factor-α (TNF-α) and inflammatory proteins inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2)) [3,6].…”
Section: Introductionmentioning
confidence: 99%